Hakikat Ilmu Kalam: Definisi, Matlamat, Metode, Topik Perbincangan dan Kedudukannya Dalam Ilmu-Ilmu Islam - al-Shafe'i, Hasan Mahmud; Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Definition is considered among the most important introduction to any science. It normally reflects our perception and influences our judgment on any particular science or knowledge; on its necessity and relevency in our life, its place and connection within other fields of knowledge and most of all on its religious status especially from an Islamic point of view. Professor Hasan al-Shafe'I presents a clear picture of Kalam by demonstrating its important definitions of all ages together with its analysis and commentaries. This is to show the very nature of Kalam, as understood by the Muslim scholars, within the Islamic tradition. It also demonstrates various aspects of Kalam and how it has developed from the earliest.